Pengaruh Konseling Humanistik Terhadap Sikap Membully Pada Siswa Kelas XI SMA Negeri 1 Sumbawa Besar - Saskia Tristanty; Wayan Tamba; Jessica Festy Maharani (Jurnal Eduforia: Jurnal Penelitian dan Pengembangan Pendidikan, 2026)
This study aims to determine the effect of humanistic counseling on the bullying attitudes of students in class XI IPA 3 at SMA Negeri 1 Sumbawa Besar. Bullying behavior in the school environment remains an issue affecting students' psychological, social, and academic aspects, necessitating a counseling approach capable of fostering individual awareness and responsibility. The study employs a quantitative approach with a pre-experimental, one-group pre-test/post-test design. The sample consisted of 10 students selected via purposive sampling. Data were collected using a bullying attitude questionnaire and analyzed using a t-test. The results show a calculated t-value of 6.443, which exceeds the t-table value of 2.262 at a significance level of 0.05. This indicates that humanistic counseling has a significant effect on reducing students' bullying attitudes. Thus, the humanistic approach can serve as an alternative guidance and counseling service to foster more positive social behavior within the school setting.